Ḥāshiyat Makhlūf al-Minyāwī ʻalá Sharḥ Aḥmad al-Damanhūrī li-matn al-Imām al-Akhḍarī al-musammá bi-al-Jawhar al-maknūn fī al-maʻānī wa-al-bayān wa-al-badīʻ wa-bi-hāmishihā Sharḥ al-Jawhar al-maknūn al-madhkūr - Minyāwī, Makhlūf ibn Muḥammad, -1878; Damanhūrī, Aḥmad ibn ʻAbd al-Munʻim. (Miṣr : al-Maṭbaʻah al-Khayrīyah, 1888)
[A metrical compendium of rhetoric, with a commentary, entitled Ḥilyat al-lubb al-maṣūn, by Aḥmad ibn 'Abd al-Mun'im al-Damanhūrī, and a supercommentary by Makhlūf ibn Muḥammad al-Badawī al-Minyāwī.].
Reproduction of the original from The British Library.
Electronic reproduction.
Keywords: Damanhūrī, Aḥmad ibn ʻAbd al-Munʻim.; Akhḍarī, ʻAbd al-Raḥmān ibn Muḥammad, -- 1512 or 1513-1575 or 1576.; Arabic language -- Rhetoric